A Descriptive Analysis of Direct Oral Anticoagulant Drugs Dosing Errors Based on Spontaneous Reports from the EudraVigilance Database - Claudiu Morgovan; Carmen Maximiliana Dobrea; Adriana Aurelia Chis; Anca Maria Juncan; Anca Maria Arseniu; Luca Liviu Rus; Felicia Gabriela Gligor; Simona Alexandrina Ardelean; Laurentiu Stoicescu; Steliana Ghibu; Adina Frum (MDPI AG, 2023)
Direct oral anticoagulant drugs (DOACs) interfere with the coagulation process, thus improving patient care for those who require anticoagulant treatment. This study presents a descriptive analysis of adverse reactions (ADRs) attributed to DOAC dosage errors (overdose, underdose, and improper dose). The analysis was performed based on the Individual Case Safety Reports from the EudraVigilance (EV) database. Results show that data reported for rivaroxaban, apixaban, edoxaban, and dabigatran are mostly regarding underdosing (51.56%) compared to overdosing (18.54%). The most dosage error reports were identified for rivaroxaban (54.02%), followed by apixaban (33.61%). Dabigatran and edoxaban had similar percentages (6.26% and 6.11%, respectively) regarding dosage error reports. Since coagulation issues can become life-threatening events, and factors such as advanced age and renal failure can influence the pharmacokinetics of drugs, the correct usage of DOACs is of utmost importance for the management and prevention of venous thromboembolism. Thus, the collaboration and the complementarity of knowledge of physicians and pharmacists may offer a reliable solution for DOAC dose management and improve patient care.